The Relationship of Disaster to the Islamic Economic System: An Analysis on Aspect of Maqāṣid Shari‘āh Framework - Muttaqin, Aris Anwaril; Samsudin, Muhammad Adib; Salleh, Ahmad Dahlan; Ahmad, Azlin Alisa (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Disasters occurring in recent years across various parts of the world have affected the economy and social life of the global community. Although disaster economics has received prominent attention from scholars, studies adopting the maqāṣid shari‘āh approach remain limited. Therefore, this study aims to analyze the relationship between disasters and the economic system contained in Surah Yusuf based on the maqāṣid methodology and framework. The data were collected via document analysis and in-depth interviews with three experts from different disciplines to assess the reliability of the findings based on Cohen’s Kappa test. The data analysis was based on the maqāṣid methodology involving four stages: identification of verses concerning disasters and economic system, a reflection of the verses using themaqāṣid framework, critical literature studies, and formation of principles about disasters in the Islamic economic system. The findings show that the relationship between disasters to the Islamic economic system can be understood based on maqāṣid shari‘āh. In this regard, disasters that are detrimental to the community's economy from a positive economics perspective have provided many lessons to improve the economic agents’ behavior from a normative economics view based on the maqāṣid framework. The findings further depict that, the majority of past studies on disaster economics were conducted using a positive-materialist approach. Therefore, this study offers a new perspective on the relationship between disasters and the economic system by understanding the material and non-material reality based on the guidance of revelation.